THE RELATIONSHIP BETWEEN MOTHER’S ROLE AND THE INCIDENCE OF DENTAL CARIES IN ELEMENTARY STUDENTS GRADE 1, 2 AND 3 SDN 099 BABAKAN TAROGONG BANDUNG - -, Titus; Sinaga, Anni; Melia, Stephanie (STIK Immanuel Bandung, 2019)
Teeth are body tissues that are easily damaged. Dental caries will occur if there is lack of treatment. Mother has an important role to provide guidance and supervision of the incidence of dental caries in children of school aged 6-12 years. This study aims to determine the relationships between mother’s role with the incidence of dental caries school aged childrenn (grade 1 -3). This study used a quantitative research method with a cross sectional approach. Simple random sampling is used to gather data from 85 mother and children. The mother’s role was collected using 30 items questionnaire, and observation sheets used fordental caries incidence. The result indicates that more than half role of mothers is categorized as poor (52.9%) and good (47.1%). The observation showed that children who experienced dental caries were 85.9% and those who did not experience dental caries were 14.1%. The results of the chi test showed no relationship between the role of the mother and the incidence of dental caries (p value 0.248 (> 0.05). It is recommended for Public Health Center and nurses to conduct health promotion on dental health, and for schools to carry out regular toothbrush activities at least once every three months and carry out regular dental checks at least every six months. Keywords : Mothers’ Role, Dental Caries, School Aged Children